حق المساواة في الفقه الإسلامي والمواثيق الدولية - ولد خسال، سليمان (المركز الجامعي أمين العقال الحاج موسى أق أخموك لتامنغست - معهد الحقوق والعلوم السياسية, 2013)
يعالج هذا الموضوع مبدأ وحق المساواة في الفقه الإسلامي والمواثيق الدولية، ويصل إلى أن هذا الحق مكفول في الجملة بين الشريعة الإسلامية والمواثيق الدولية، وإذا كان حق المساواة في إطار المواثيق الدولية قد سبق إليه الغرب شكلا وصياغة، إلا أن مضمونه وحقيقته إنما تحقق قبل ذلك من خلال نصوص الإسلام الواضحة والصريحة، ولعل مما يعاب على حق المساواة في الفكر الغربي اعتماده على ما يعرف بالمساواة المطلقة، فضلا عن الشكلية وبعدها عن المساواة الفعلية، أما حق المساواة في الفقه الإسلامي فهي شكلية جسدها على أرض الواقع شعائر وعبادات الإسلام. ويظهر أن الشبهات التي يعترض بها البعض كون أحكام الشريعة الإسلامية تخل بمبدأ المساواة بين الجنسين، فإن هذا يعود إلى جهل ملابسات الحكم، (وهو ما حاولت هذه المداخلة توضيحه بأمثلة عملية)، ويبقى في الأخير التأكيد على ضرورة قيام كل المشارب بترقية مبدأ المساواة من أجل الإسهام في الحضارة الإنسانية، وعلى الغرب أن يستفيد من المخزون الشرعي الموجود في الفقه الإسلامي، لا أن يتعامل معه بعقلية الإقصاء، وعلى العالم الإسلامي أن ينظر إلى المواثيق الدولية كتراث مشترك وبعقلية واقعية
Addresses this topic principle of the right to equality in Islamic jurisprudence and international conventions, and up to that this right is guaranteed in the sentence between Islamic law and international conventions, and if the right to equality in the framework of international conventions have already been to the West in form and formulation, but the content and what it is, but check before that of During the texts of Islam Allowadhhoabihh, and perhaps maligned than the right to equality in Western thought its dependence on what is known as absolute equality, as well as formal and distance from the de facto equality, the right to equality in Islamic jurisprudence are pro forma her body on the ground and worship rites of Islam. It appears that the suspicions which objected by some that the provisions of the Islamic Sharia without prejudice to the principle of equality between the sexes, this is due to the ignorance of the circumstances of the judgment, (which is what I tried this intervention illustrated with practical examples), and remains in the latter emphasized the need for all stripes upgrade the principle of equality for contribute to human civilization, and to the west to take advantage of the existing inventory legitimate in Islamic jurisprudence, does not have to deal with the mentality of exclusion, and the Islamic world to look to international conventions as a common heritage and mentality realistic
Keywords: الفقه الإسلامي -- التشريع الإسلامي -- الأحكام الشرعية -- المعاهدات والمواثيق الدولية -- المساواة بين الرجل والمرأة -- حق المساواة -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث -- اللغات الأجنبية